Islamic feminism: A perfect match or a contradiction in terms? - Aboul-Ezz, Merna (AUC Knowledge Fountain, 2017)
Gender inequality is a global issue that limits women’s social, economic as well as political opportunities. Fortunately enough, there have been many feminist movements that fight for gender equality and women’s rights. The basis for male domination is sometimes justified by culture, or religion. The problem arises when the oppression of women is being justified on the basis of religion mainly Islam in the Arab countries, for it becomes harder to women to challenge the situation, because it conflicts with their inner faith. This thesis will tackle the issue of Islamic Feminism, a recent movement that calls for gender equality in the name of Islam, through providing an alternative feminist interpretation of the Qur’anic text as well as Islamic Law. Although Islamic Feminists have succeeded in using their interpretation to reform laws that address women’s issues in the Muslim countries, they still face many challenges from traditional scholars who have attained Islamic education and have studies Islamic jurisprudence. Consequently, this paper argues that in order to move a step forward, and for the movement to be more effectively successful, Islamic feminists have to engage with the traditionalists, to increase the movement’s credibility as well as legitimacy and to be able to make the changes they long for come true.